The Chemiexcitation of the Chemiluminescence of Lophine Peroxide Anions via a Partially Cyclic Transition State. Issue 6 (12th December 2013) - Lu, Gonghao; Wada, Jun; Kimoto, Takashi; Iga, Hiroshi; Nishigawa, Hideki; Kimura, Masaru; Hu, Zhizhi
Abstract: It was shown that acyclic intermediates play a role in the chemiexcitation of the chemiluminescence (CL) of lophine peroxides in addition to the dioxetane intermediates. Because the CL efficiencies of position‐isomers ( R )‐9 and ( R )‐10, which theoretically give the common dioxetane intermediate, were different, the different CL efficiencies are attributable to the CL mechanism involving a partially cyclic transition structure at the chemiexcitation step. Abstract : The study of isomeric 2‐phenyl‐4‐ p ‐X‐phenyl‐5‐ p ‐Y‐phenyl‐4‐silylated peroxy‐isoimidazals [( R )‐9 : X = CF3, Y = F and ( R )‐10 : X = F, Y = CF3 ] confirmed the existence of lophine peroxide anion intermediates in the chemiluminescence of lophine peroxides in addition to the dioxetane intermediates.